Ethics Unbound: Islam and the Philosophy of Taha Abdurrahman - Tarik ElFalih (International Journal of Scientific Research and Innovative Studies, 2025)
The paper rigorously analyses the notion of Islamic modernity as defined by the Moroccan philosopher Taha Abdurrahman, highlighting his distinctive synthesis of intellectual liberty, spiritual profundity, and moral rejuvenation. Abdurrahman's framework is articulated as a persuasive counter-narrative to dominant Western-centric and secular paradigms of modernity, establishing its alternative foundation in Islamic metaphysics and moral philosophy (Abdurrahman, 2006).Utilising postcolonial theory, Sufi philosophical traditions, and the debate on various modernities (Eisenstadt, 2000; Appadurai, 1996; Said, 1979), this paper situates Abdurrahman's approach within a wider context of global intellectual difficulties. It contends that his technique offers Muslim communities in the Global South and the diaspora a substantial framework to address matters of cultural authenticity, dignity, and identity in the modern context. Keywords: Modernity, Spirit, Location, Majority, Universality, Critique. Received Date: August 21, 2025 Accepted Date: September 13, 2025 Published Date: October 01, 2025 Available Online at <a href="https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/459" target="_blank" rel="noopener" data-saferedirecturl="https://www.google.com/url?q=https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/410&source=gmail&ust=1759417452501000&usg=AOvVaw1l7OC6UWWzjhjztIoCVZr6">https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/459